Durability Studies on Fly Ash Based Geopolymer Mortar Under in Ambient Curing Condition - Sreevidya, V.; Anuradha, R.; Thomas, Tini; Venkatasubramani, R. (Asian Journal of Chemistry, 2012)
Present paper reports the experimental results of a study conducted to assess the durability of fly ash based geopolymer mortar in adverse environments. In this study, sodium hydroxide and sodium silicate solution were used as alkaline activators. The ratios between solution (NaOH, Na2SiO3 solution and water) to fly ash were 0.376, 0.386, 0.396 and 0.416 by weight. Geopolymer mortar cube specimens of 50 mm × 50 mm × 50 mm were cast with a ratio of fly ash to sand as 1:2.5 by weight. The binder solution consists of a combination of sodium hydroxide and sodium silicate solution in the ratio of 1:2.5. The cubes were cured in ambient condition. The various durability tests like saturated water absorption and acid resistance against 5 % HCl and 5 % HNO3 were performed on these specimens. The compressive strength after acid resistance was found out and compared with the compressive strength obtained at 28 days. The results obtained from this study indicated that the geopolymer mortar specimens are highly resistant to acids.